TURKISH ELECTIONS BETWEEN SLEDGEHAMMER THE CONSTITUTION AND ANVIL OF THE PARTIES THE ELECTIONS OF :(1946,1950,1961) AS EXAMPLE - Asst.Lect Katib Mohamed Gavel (Journal of College of Education, 2025)
Parliamentary life in Turkey took long steps to establish itself. The parliamentary government was launched for the first time in 1876 , and it had grown in response to the process of external pressures 1920, The Turkish legislature has greatly excelled in several areas , the most important of which are parliamentary immunity, parliamentary inviolability, independence of procedures freedom of protest , and the right to meet at any time decided by its members In the years 1961-1980, and thus made it clear that Parliament has an independent and somewhat professional membership, but there is a contradiction to what we have mentioned , as there is an inverse movement in the constitutional position of Parliament in the system that dates back to the years 1921 and 1922, which granted the Council the right to exercise its independence was set aside in the 1961 Constitution, and as a result, the Council became just one of the institutions that could exercise that right , With the end of his theoretical sovereignty, other bodies such as the executive body and the judiciary took their share in the exercise of independence, as the executive authority became more clearly independent from the legislative authority and obtained important powers based on the capabilities it acquired under the constitution.